2014
DOI: 10.1111/asj.12334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beet pulp supplementation on growth performance, fecal moisture, serum hormones and litter performance in lactating sows

Abstract: This study was conducted to evaluate effects of beet pulp supplementation on growth performance, fecal moisture, serum hormones and litter performance in lactating sows. Ninety primiparous sows (Landrace × Yorkshire) were randomly allotted to one of three dietary treatments in a 21-day trial starting 3 days before parturition. The three dietary treatments were supplemented with 0, 10 and 20% beet pulp, respectively. Backfat loss and fecal moisture content were increased (P < 0.05), where cortisol and norepinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Notably, no statistically significant distinctions were observed in terms of sow BW, BWL, BFT, BCS before farrowing and after farrowing, and at weaning. These findings align with the outcomes of [15], who noted that the inclusion of 10% and 20% sugar beet pulp (SBP) in the diet did not yield significant effects on sow growth performance, BFT, BCS, or ADG. Similarly, the addition of 20% supplementation of wheat bran (WB), soybean hulls (SH), or rice hulls in diets did not result in any significant impact on reproductive performance of sows during both gestation and lactation phases [16].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, no statistically significant distinctions were observed in terms of sow BW, BWL, BFT, BCS before farrowing and after farrowing, and at weaning. These findings align with the outcomes of [15], who noted that the inclusion of 10% and 20% sugar beet pulp (SBP) in the diet did not yield significant effects on sow growth performance, BFT, BCS, or ADG. Similarly, the addition of 20% supplementation of wheat bran (WB), soybean hulls (SH), or rice hulls in diets did not result in any significant impact on reproductive performance of sows during both gestation and lactation phases [16].…”
Section: Discussionsupporting
confidence: 86%
“…Although the sequence of events leading to reduced stillbirth rate cannot be explicitly described from the present study, 2 modes of action of DF on the stillbirth rate may likely be involved. First, sows that were fed high DF in late gestation would less likely develop constipation before parturition due to increased intestinal activities and the high water-holding capacity of the DF (Oliviero et al, 2009;Krogh et al, 2015;Zhao et al, 2015), and water in the colon digesta in turn increases the softness of the feces. According to Krogh et al (2015), sows supplemented with high DF have a greater incidence of soft feces at farrowing than their nonsupplemented counterparts (68 vs. 29%, respectively; P = 0.04), and this is in line with what Oliviero et al (2009) reported.…”
Section: Dietary Fiber and Impact On Litter Size And Piglet Mortalitymentioning
confidence: 99%
“…To concur, a related study concluded that the inclusion of dietary fiber in the sows' gestation diet was beneficial in boosting postprandial satiety and reducing stress and abnormal behavior in sows (Huang et al, 2020). Besides, supplementation of beet pulp in the diets of lactating sows led to a decrease in their cortisol and norepinephrine levels (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%